1987
DOI: 10.1097/00000658-198705000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Mastopathy in Insulin-dependent Diabetics

Abstract: A type of mastopathy is unique to insulin-dependent diabetic patients. The characteristic change is a connective tissue overgrowth with vasculitis and some proliferation of duct epithelium. It is not the type of change typically associated with an increased risk of breast cancer. Clinically this change is indistinguishable by physical or radiographic findings from breast malignancy. Eleven biopsies showing these characteristics were performed on insulin-dependent patients who had diabetes mellitus from childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
1
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 4 publications
6
35
1
1
Order By: Relevance
“…On the mammography, they may or not be visible. In the eight cases described by Byrd et al (25), it was difficult to make the diagnosis and breast cancer was the differential diagnosis, as it happened to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…On the mammography, they may or not be visible. In the eight cases described by Byrd et al (25), it was difficult to make the diagnosis and breast cancer was the differential diagnosis, as it happened to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Mammography shows the presence of a dense parenchymal structure with no distortions or microcalcifications 5,6) . Ultra- sound findings vary from irregular hypoechoic mass with marked acoustic shadowing to a vague hypoechoic area without shadowing 5,6,8) . These appearances are nonspecific and mimic those of scirrhous or invasive lobular carcinoma 19,20,33) .…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, most researchers have reported that diabetic mastopathy usually occurs in patients who have suffered from type diabetes mellitus of long duration [4][5][6][7] . Although there have been some reports of diabetic mastopathy in a patient with type diabetes mellitus, there have been few cases in non-insulin dependent patients 3,[8][9][10][11][12] .…”
mentioning
confidence: 99%
“…Seidman et al 6) reported a mean duration of longer than 13 years (range 4 -27 years) for diabetic mastopathy to develop. Mammographic appearances show the presence of a dense parenchymal structure with no distortions or microcalcifications 7,12) . Ultrasound findings vary from irregular hypoechoic mass with marked acoustic shadowing to a vague hypoechoic area without shadowing 7,12) .…”
Section: Case Reportmentioning
confidence: 99%